EVT524: Emission Control Technology / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (Universiti Teknologi MARA (UiTM), 2020)
This is a graduate course oriented to provide graduate students with the knowledge and skills for understanding and implementing appropriate air pollution control strategies. The course covers the main methodology on control of gases and particulate from the combustion, industrial processes and mobile sources. The control techniques and current technologies to reduce the pollutants emission in the atmosphere are emphasized.